Techno-economic optimization of hybrid renewable energy systems for household energy management - Pasaribu, Faisal Irsan; Suwarno, Suwarno; Hardi, Surya; Taufik, Ahmad; Panjaitan, Albert; Andri, Aimil Musfi; Aulia, Muhammad Reza (Institute of Advanced Engineering and Science, 2025)
Housing is a private palace that is safe, comfortable, and private. Techno-economic optimization of hybrid renewable energy systems and energy management for realizing green energy is a fundamental concept for ensuring security, comfort, and privacy in green housing for its residents, enabling them to carry out activities in their environment. The application of techno-economic optimization and renewable energy management to manage electrical energy so that it can be saved so that electricity costs can be reduced as one of the energy efficiency models. The problem of waste emissions and environmental pollution cannot be avoided. Therefore, a techno-economic optimization model for integrated power generation is needed, which is environmentally friendly and related to the housing problem discussed in this study. This study supports the concept that hybrid housing development is the best way to address environmental pollution, emissions, and waste in future housing and can be used as a benchmark for future housing development. In addition, the techno-economics of renewable energy used in households was also discussed.